Hormone replacement therapy in women with history of thrombosis or a thrombophilia. Issue 1 (March 2023) - Morris, Guy; Talaulikar, Vikram
Findings from the Women's Health Initiative (WHI) randomised placebo-controlled trial (RCT) were published at the beginning of this century. They suggested that hormone replacement therapy (HRT) use increased the risk of cardiovascular disease and venous thromboembolism including pulmonary embolism and deep vein thrombosis The findings led to a decline in HRT prescriptions and negative publicity about the use of HRT for women with significant menopausal symptoms. Subsequent studies have shown that the risk of thrombosis with HRT relates to whether estrogen is combined with a progestogen and the route of administration of estrogen. In healthy women with no background medical problems, transdermal hormone replacement is not associated with an increased risk of thrombosis. However, much less is known about the safety of various HRT preparations in women with a high background risk of thrombosis. These cases can often be challenging for clinicians with uncertainties around testing for thrombophilia, use of anticoagulation and striking a balance between the risks and benefits of prescribing HRT. This article will review the mechanism of thrombosis with differing types of HRT and present the evidence from the relevant trials. The article will also present the evidence that specifically relates to women with a personal history of thrombosis or thrombophilia (heritable and acquired) to enable clinicians to better individualise the risk assessment for each woman requesting HRT and understand the role of thrombophilia screening or concomitant anticoagulation in such situations.